GAJAH DALAM TERAKOTA MAJAPAHIT - Prima Yustana (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2011)
Elephant’s manifestation in the shape of Majapahit’s terracotta more interesting with aesthetic approach. The artifact is an discovery of archeologists’ in Trowulan which is estimated as a city center of Majapahit Kingdom. Many manifestations of the elephant are interested to be observed. Many findings, so far, will be observed especially from art. To increase the accuracy in the analysis process, data searching is conducted to the relief on Hindu and Buddha temples, so, hopefully, it can be understood the background why the animal appears in the Indonesian art and, especially, why there is also the manifestation of the animal in the shape of terracotta in Trowulan. Elephant manifestation in terracotta is considered to have many functions and symbolical meanings in religion. Terracotta has been known as an ancient human creation. The using of terracotta in Indonesia achieved its triumph in the classic period which was 13–15 century A.D., along with the golden age of Majapahit Kingdom. The materials in the research use the basic of aesthetics and iconography sciences because the artifact has art shape structure related to beauty and aesthetics. To find out the functions and the meanings in the relation religious activities, the discussions are focused in terracotta artifact manifested in statue and other things so iconographic science very supports to find out what meaning exist in the elephant manifestation. Elephant, in its shape, is manifested realistic and deformatif. Both manifestations have the background of the belief from Trowulan society in Majapahit period, which had Hindu and Buddha in their religion. In the period, elephant was considered to have symbol of strength, virility and wisdom. Besides that, elephant was also the vehicle of God Indra, named Airavata. Elephant is also the symbol of Budha’s birth story (Jataka). Elephant was also considered as God, called Shri-gaja. The last, elephant was also considered as a symbol of social status and fertility because elephant was a king’s pet and was used for war,so only the rich persons were able to have the animal.Keywords: Elephant, Majapahit’s terracotta, function and meaning.